The School Biography as an Instrument for Reflection on the Prior and Constructed Knowledge during Teacher Education in Terms of "How to Teach" - Zárate Montero, María Jesús (2016)
This article is a literature review, which aims at analyzing narrative as a teacher training device for university students, which through the description and analysis of their school biography, reflects on what it means to be a teacher and how and what to teach. The consulted authors conclude that this task of learning can be developed with students starting their major and those doing their teaching practicum at the end of it. The key action to be promoted is being aware of conceptions built throughout life in the role and work of a teacher and how these can influence the actions of future educators.